Module 3: the process of e-learining implementation - Terra, Ana Lúcia (2023)
E-learning, also known as online learning or digital learning, can be described as the use of technology to deliver educational content and training programs remotely. The implementation of e-learning has become increasingly popular in recent years, as it provides learners with greater flexibility and access to education. The process of implementing e-learning can vary depending on the specific needs of an organization or educational institution (Clark & Mayer, 2011). However, the implementation of e-learning typically involves a multi-step process that includes needs assessment, technology selection, content development, implementation, delivery, and evaluation. This process supports those who design e-learning services and content. The effectiveness of e-learning programs can be measured through assessments, surveys, and focus groups to gather feedback from the learners and measure the impact of the program. This paper systematizes structured, robust and solid guidelines for a sustainable approach to the effective design and implementation of e-learning, and the presentation of a module on e-learning implementation is the core of this chapter. Focusing on the implementation of e-learning, this module is intended to deconstruct into five learning units the activities that are needed to develop an e-learning course, from identifying the organisational requirements, presenting instructional design methodologies, explaining pedagogical techniques and demonstrating the use of digital tools to enhance learning experiences. For this purpose, e-learning is understood as a way of learning in which technology plays a vital role in supporting the interaction between learning partners (students, teachers and academic staff) in order to improve, or at least favour, the cognitive and social processes of learning (Basak, Wotto, & Bélanger, 2018). One of the primary benefits of e-learning is that it enables learners to access content from anywhere, at any time. This can be particularly beneficial for individuals with hectic schedules or that live in remote areas where access to traditional classroom education is limited.